2001
DOI: 10.1002/jgm.172
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced gene delivery to human airway epithelial cells using an integrin-targeting lipoplex

Abstract: These results indicate that integrin-binding peptides represent one way to enhance liposome-mediated gene delivery to pulmonary epithelia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 36 publications
1
21
0
1
Order By: Relevance
“…We have previously shown that a peptide containing an integrin-binding RGD motif can enhance liposomemediated gene expression in 16HBE cells [28]. To determine if an integrin-binding domain and a NLS domain could enhance gene delivery more than each separate component we tested a bipartite VP1-RGD peptide.…”
Section: A Vp1-rgd Chimeric Peptide Does Not Enhance Liposome-mediatementioning
confidence: 99%
“…We have previously shown that a peptide containing an integrin-binding RGD motif can enhance liposomemediated gene expression in 16HBE cells [28]. To determine if an integrin-binding domain and a NLS domain could enhance gene delivery more than each separate component we tested a bipartite VP1-RGD peptide.…”
Section: A Vp1-rgd Chimeric Peptide Does Not Enhance Liposome-mediatementioning
confidence: 99%
“…Thus, this approach allows to discriminate between extracellularly bound and internalized complexes. 44,45 Indeed, the number of fluorescence positive cells decreased 20% after additional incubation of CellsScrub washing buffer (cellular internalization) compared to the number of fluorescence positive cells after washing with PBS (cellular association) alone. Similar observations were made for the mean fluorescence intensity with a decrease of 32%.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that EGFmodified lipid vesicles were constructed for effective delivery to tumor cells expressing high levels of the EGF receptor (Kikuchi et al 1996). A similar approach has been used for transferrin or lactoferrin with their receptors, and the RGD peptide with integrins (Cheng 1996;Elfinger et al 2007;Kunath et al 2003;Rao et al 2008;Scott et al 2001). In this regard, Siglecs also exhibited enhanced efficiency of uptake of binding substances.…”
Section: Discussionmentioning
confidence: 99%